PERBEDAAN HASIL BELAJAR EKONOMI SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DENGAN PEMBELAJARAN KONVENSIONAL DI KELAS X SMA NEGERI 1 SUNGAI AUR KABUPATEN PASAMAN BARAT - Sistria, Enda Anggraini; Wahyuni, Sri; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
The background of this research by studying the results of the low economic class X SMA N 1 Sungai Aur Academic Year 2013/2014 . This is caused by the lack of activity of students in the learning process . This study aimed to determine differences in the economic outcomes of students with learning cooperative learning model Make A Match with conventional learning in class X SMAN 1Sungai Aur . This type of research is experimental research . The study population was a student of class X SMA N 1 Sungai Aur academic year 2013/2014. Samples were taken by purposive sampling technique, was chosen as the experimental class class X2 and X3 as grade control class. The instrument used is the achievement test . Techniques of data analysis was to test the hypothesis t test . Based on the analysis of data obtained by the average value of the experimental class average of 76.5 and 67.8 classroom control . Results of data analysis known tcount 3,081 greater than the mean price of 1,960 ttable hypothesis is accepted at significance level α = 0.05 . It can be concluded that the results of the economic study of students with cooperative learning model Make A Match better than economics student learning outcomes in the conventional learning process in class X SMA N 1 Sungai Aur . Keywords : Cooperative Learning Model Make A Match Type , ModelConventional Learning , Learning Outcomes